Creative Journaling for Teachers : A Visual Approach to Declutter Thoughts, Manage Time and Boost Productivity - Carter, Nichole (Book collections on Project MUSE., 2022)
"We are living in an age when "hustle" and "grind" are part of our daily lives. While teachers are expected to stay on top of their lengthy to-do list, the demands on them are greater than ever. How can we provide the tools teachers and, by extension, their students need to declutter thoughts, manage time better, and remain focused and productive? With her approachable style, educator and trainer Nichole Carter demonstrates how unlocking the creative brain can help improve mental health and problem-solving ability, as well as lead to better self-awareness and time management. Filled with the author's original illustrations, the book shares ideas and techniques for developing an effective, personalized system to improve productivity and address teacher burnout. The book can also help teachers help students - particularly those in older grades - prioritize and think through their thoughts, goals and actions to be more productive learners. Throughout the book, readers will be presented with challenges and "try this" moments that will encourage them to write in the book and reflect"--